2022
DOI: 10.3390/jcdd9060188
|View full text |Cite
|
Sign up to set email alerts
|

Extracardiac Vagal Stimulation-Assisted Cardioneuroablation: Dynamically Evaluating the Impact of Sequential Ganglionated Plexus Ablation on Vagal Control of SAN and AVN in Patients with Sinoatrial Node Dysfunction

Abstract: Cardioneuroablation (CNA) is proposed as a promising therapy for patients with sinoatrial node dysfunction (SND) that is mediated by excessive vagal tone. However, a series of urgent questions about CNA remain unanswered. From December 2020 to March 2022, six patients with symptomatic SND who underwent CNA were summarized in this report. Sequential CNA targeting Ao-SVC GP, PMLGP, RAGP, and LSGP was performed in patients, guided by fractionated intracardiac electrograms and dynamically evaluated by extracardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The cell bodies of cardiac efferent vagal postganglionic neurons have been shown to be contained in the intrinsic cardiac GP, which is embedded in the atrial wall and in epicardial fat pads ( 10 , 11 ). Common GPs include Ao-SVC GP, PMLGP, RAGP, RIGP, LSGP, and LIGP with different physiological functions, and they interact with one another ( 6 , 9 , 10 ). Therefore, a disruption of nerve fibers by radiofrequency ablation can inhibit excessive activation of the vagal nerve, thereby eliminating or improving clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The cell bodies of cardiac efferent vagal postganglionic neurons have been shown to be contained in the intrinsic cardiac GP, which is embedded in the atrial wall and in epicardial fat pads ( 10 , 11 ). Common GPs include Ao-SVC GP, PMLGP, RAGP, RIGP, LSGP, and LIGP with different physiological functions, and they interact with one another ( 6 , 9 , 10 ). Therefore, a disruption of nerve fibers by radiofrequency ablation can inhibit excessive activation of the vagal nerve, thereby eliminating or improving clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Most efferent cardiac vagal fibers to the atrium, sinus node, and atrioventricular node pass through this area and then project onto the RAGP (Armour et al, 1997;Chiou et al, 1997). A recent study confirmed that the ablation of SVC-Ao GP significantly increased the heart rate, while elimination of vagal response evoked by extracardiac vagal stimulation (Chen et al, 2022). The RAGP and SVC-Ao GP were considered more valuable candidate targets to modulate sinus node function in symptomatic SND patients when compared with other GPs.…”
Section: Figurementioning
confidence: 99%
“…In clinical practice, the reproduction of cardioinhibition is achieved through the HUTT, and in the laboratory, the sole method capable of replicating a similar controlled condition is ECVS. 10,19,23 Both in spontaneous events and during the HUTT, there is a massive vagal response simultaneously affecting all regions with vagal innervation, particularly the sinus node, AV node, and atrial walls. This condition can be readily reproduced with ECVS as many times as necessary, depending on the operator, as illustrated in Figure 2A,B.…”
Section: Rationale Of Extracardiac Vagal Stimulationmentioning
confidence: 99%
“…Furthermore, cardioinhibition typically involves a substantial bilateral vagal response, and the control method must replicate it as closely as possible. In clinical practice, the reproduction of cardioinhibition is achieved through the HUTT, and in the laboratory, the sole method capable of replicating a similar controlled condition is ECVS 10,19,23 . Both in spontaneous events and during the HUTT, there is a massive vagal response simultaneously affecting all regions with vagal innervation, particularly the sinus node, AV node, and atrial walls.…”
Section: Rationale Of Extracardiac Vagal Stimulationmentioning
confidence: 99%